Analisis Keuntungan dan Nilai Tambah Usaha Keripik Singkong pada Usaha Home Industri â€œTiga Putra Sundaâ€ di Desa Sindangkasih Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Wulandari, febri; Abdi, Abdi; Rosmawaty, Rosmawaty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine how much benefit and value added obtained from processing of cassava into cassava chips with two variants of taste (saltiness and flavor Balado) made the home business industry